The Anti-Inflammatory and Neuroprotective Effects of Ghrelin in Subarachnoid Hemorrhage-Induced Oxidative Brain Damage in Rats - VELİOĞLU ÖĞÜNÇ, AYLİZ; YEGEN, BERRAK; ERZİK, CAN; AKAKIN, DİLEK; ÇETİNEL, ŞULE; TETİK, ŞERMİN; ÖZDEMİR KUMRAL, ZARİFE NİGAR (MARY ANN LIEBERT, INC, 2010)
To elucidate the putative neuroprotective effects of ghrelin in subarachnoid hemorrhage (SAH)- induced brain injury, Wistar albino rats (n=54) were divided into sham-operated control, saline-treated SAH, and ghrelin-treated (10 mu g/kg/d IP) SAH groups. The rats were injected with blood (0.3mL) into the cisterna magna to induce SAH, and were sacrificed 48 h after the neurological examination scores were recorded. In plasma samples, neuron-specific enolase (NSE), S-100 beta protein, TNF-alpha, and IL-1 beta levels were evaluated, while forebrain tissue samples were taken for the measurement of malondialdehyde (MDA), glutathione (GSH), reactive oxygen species levels, myeloperoxidase (MPO), Na+-K+-ATPase activity, and DNA fragmentation ratio. Brain tissue samples containing the basilar arteries were obtained for histological examination, while cerebrum and cerebellum were removed for the measurement of blood-brain barrier (BBB) permeability and brain water content. The neurological scores were impaired at 48 h after SAH induction, and SAH caused significant decreases in brain GSH content and Na+-K+-ATPase activity, and increases in chemiluminescence, MDA levels, and MPO activity. Compared with the control group, the protein levels of NSE, S-100 beta, TNF-alpha, and IL-1 beta in plasma were also increased, while ghrelin treatment prevented all SAH-induced alterations observed both biochemically and histopathologically. The results demonstrate that ghrelin alleviates SAH-induced oxidative brain damage, and exerts neuroprotection by maintaining a balance in oxidant-antioxidant status, by inhibiting proinflammatory mediators, and preventing the depletion of endogenous antioxidants evoked by SAH.
Keywords: cerebral vasospasm; ghrelin; lipid peroxidation; neuron-specific enolase; oxidative stress; subarachnoid hemorrhage; S-100 beta; NEURON-SPECIFIC ENOLASE; REMOTE ORGAN INJURY; CEREBRAL VASOSPASM; CEREBROSPINAL-FLUID; HEAD-INJURY; ISCHEMIA-REPERFUSION; RADICAL SCAVENGER; ACYLATED PEPTIDE; REACTIVE OXYGEN; PROTEIN S-100B